2013
DOI: 10.5402/2013/109034
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Related Acute Kidney Injury: Experience of the Nephrology Unit at the University Hospital of Fez, Morocco

Abstract: Introduction. Acute kidney injury (PRAKI) continues to be common in developing countries. The aim of this paper is to study AKI characteristics in pregnancy and identify the factors related to the unfavorable evolution. Methods. This prospective study was conducted in the University Hospital Hassan II of Fez, Morocco, from February 01, 2011 to January 31, 2012. All patients presenting PRAKI were included. Results. 37 cases of PRAKI were listed. Their ages varied from 20 to 41 years old, with an average of 29.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
50
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 15 publications
7
50
2
1
Order By: Relevance
“…10,11 There was one (6.6%) maternal mortality in our study compared to 2.7% in the Moroccan study and 20% in the study by Najar et al 10,11 …”
mentioning
confidence: 44%
See 1 more Smart Citation
“…10,11 There was one (6.6%) maternal mortality in our study compared to 2.7% in the Moroccan study and 20% in the study by Najar et al 10,11 …”
mentioning
confidence: 44%
“…10 In our series, PRAKI was more frequent in the postpartum period (93.3%). This is probably a reflection of reduction in cases in early pregnancy due to legalization of abortion and improving antenatal care.…”
Section: 11mentioning
confidence: 76%
“…8 In our study, the average age was 29.03±6.3 years, ranging from 18 to 40 years. The mean serum creatinine was 34.8mg/L±25.4 with a maximum value of 105mg/L and a minimum value of 14mg/L.…”
mentioning
confidence: 59%
“…Caring for women diagnosed with acute kidney injury is a real challenge for nephrologists and all the medical team. 8 AKI usually occurs in the third trimester of pregnancy. Puerperal sepsis and thrombotic microangiopathy are seen in the postpartum period.…”
Section: Graph 3: Causes Of Death (N=11)mentioning
confidence: 99%
“…In United States, Solomon et al indicated that a diet rich in fruits and vegetables would be as effective as the intake of specific food supplements to fight the metabolic acidosis responsible for exposure to kidney disease [9]. About 5.26% of the patients had HBP.…”
Section: Discussionmentioning
confidence: 99%